THE CHARACTERISTICS AND DEVELOPING AN ASSESSMENT INSTRUMENT OF HIGH ORDER THINKING SKILL (HOTS) ITEMS WITH 4-D MODELS - Mahmudati, Rina (Universitas Tanjungpura, 2023)
The 21st century learning aims to develop and improve the process of high order thinking in students, including when solving mathematical problems. This research will discuss the characteristics and developing an assessment instrument of HOTS (high order thinking skill) items. The method used is research and development method with 4-D models (define, design, develop, disseminate). Scoring in Politomus scale was used and analyzed by Partial Credit Model 1 Parameter Logit (PCM 1-PL). Results of the research is 20 test items there are 17 items that qualify as a good items views of validity and reliability. Results based the criteria of Infit Mean Square is 1.00 and a standard deviation of 0.17 indicates test items fit with Partial Credit Model (PCM). Reliability items indicated by Cronbach's Alpha coefficient was 0.79 with the very reliable category. Test items validity based on the empirical analysis showed there are 17 valid test items with 12 test items as good categorized 5 test items as good enough category.